Can AI Predict Patient Deterioration in Hospital Settings? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Patient deterioration in hospital settings is a critical issue that can lead to adverse events, including increased morbidity and mortality. Early identifica...
Keywords: AI in Clinical Decision Support; Predict; Patient; Deterioration; Artificial Intelligence; Machine Learning; Healthcare